Wybrane ćwiczenia emisyjne w pracy profilaktyczno-terapeutycznej = Selected emission exercises in prophylactic and therapeutic work - Kataryńczuk-Mania, Lidia; Pusztuk-Mania, Małgorzata (Zielona Góra: Instytut Pedagogiki. Wydział Pedagogiki, Psychologii i Socjologii. Uniwersytet Zielonogórski)
The article contains proposals for selected exercises and games in the field of voice emission. The authors emphasize the importance of using songs to improve speech in prophylaxis and rehabilitation. Presented are selected methods and techniques that can be used in therapeutic work with persons with difficulties emission, education. The presented material contains selected threads from the discussed issues.
Keywords: ćwiczenia emisyjne; Piosenka dziecięca polska - melodia z tekstem podłożonym; metody i techniki stosowane w pracy profilaktyczno- terapeutycznej; emission exercises; songs for children; methods and techniques used in the prophylaxis and therapeutic work